Compositional protein and lipid quality indices in Salak (Salacca zalacca) snack bars fortified with Moringa oleifera - ITA FATKHUR ROMADHONI; DWI IRIYANI; RITA ISMAWATI; KRISTIAN TRIATMAJA RAHARJA (Smujo International, 2026)
Abstract. Romadhoni IF, Iriyani D, Ismawati R, Raharja KT. 2026. Compositional protein and lipid quality indices in Salak (Salacca zalacca) snack bars fortified with Moringa oleifera. Asian J Agric 10 (1): g100165. https://doi.org/10.13057/asianjagric/g100165. This study evaluated whether graded incorporation of Moringa oleifera Leaf Powder (MOLP) induces coordinated remodeling of protein and lipid composition in salak (Salacca zalacca) flour-based snack bars. A completely randomized design was used with five fortification levels (0-8% w/w MOLP substitution in salak flour), each replicated in three independent batches (n = 3). Indispensable amino acid composition of the snack bars was quantified using High-Performance Liquid Chromatography (HPLC) after acid hydrolysis and pre-column derivatization. Amino acid adequacy was evaluated relative to the FAO/WHO/UNU adult reference pattern through Amino Acid Scoring (AAS). Fatty acid composition was determined by gas chromatography with flame ionization detection (GC-FID), and lipid distribution was interpreted using composite indices including the Atherogenic Index (AI), Thrombogenic Index (TI), and the n-6/n-3 ratio. MOLP fortification produced a clear dose-dependent increase in the density of indispensable amino acids. Lysine increased from 36.13 to 58.71 mg g⁻¹ protein, correcting the intrinsic lysine limitation of the fruit-derived matrix, whereas sulfur amino acids remained limiting across treatments. Fatty acid redistribution resulted in moderate increases in polyunsaturated fatty acids (up to 36.05% of total fatty acids). Composite lipid indices remained within balanced compositional ranges, with AI decreasing to 0.95, TI reaching 0.62, and the n-6/n-3 ratio maintained at 1.32 despite a constant palm oil source. These findings demonstrate that moderate MOLP inclusion (6-8%) can simultaneously modify indispensable amino acid adequacy and lipid compositional indices in a fruit-based snack matrix. Because digestibility and bioavailability were not assessed, the results represent compositional indicators rather than physiological metrics of protein quality.